RANCANG BANGUN SISTEM WEDDING ORGANIZER BERBASIS WEBSITE PADA NIA CATERING - Taufik, Taufik Nur Iskandar; Maulana, Aras; Haiqal, Muhammad Rafly; Wijianto , Ragil (Informatics and Computer Engineering Journal, 2022)
Wedding organizer is a service that helps to prepare and carry out wedding events in accordance with a series of wedding events that have been set and arranged according to a pre-made schedule. There are still many wedding organizer companies that still use conventional ways of running their business. It is very time consuming and inefficient. Therefore, new habits are needed in carrying out business activities. This is expected to facilitate promotional activities and shorten the transaction activities for ordering wedding organizer services. Then a proposal appears that will produce a website-based wedding organizer ordering information system. This website is designed using the PHP programming language and uses frameworks such as CodeIgniter, Bootstrap, CSS. Using PHP MySQL as database. In addition, it uses the UML (Unified Modeling Language) modeling method which consists of use case diagrams, activity diagrams, class diagrams and others. This proves that this wedding organizer booking website can run according to the expected plan.